2004
DOI: 10.1002/ejic.200300754
|View full text |Cite
|
Sign up to set email alerts
|

(μ‐Methylene)bis(methylzirconocene): Preparation, Molecular Structure, and Thermal Disproportionation

Abstract: The title compound [(µ-CH 2 )(ZrCp 2 Me) 2 ] (4) was prepared by the reaction of [Cp 2 Zr(Cl)Me] (6) with CH 2 (MgBr) 2 (5) or (CH 2 Mg) n (7). It had been expected that the carbon atom bridging the two zirconium atoms of 4 might be a candidate for a planar tetracoordinate carbon atom, but the X-ray crystal structures of two different modifications (crystals 1 and 2) showed it to be non-planar; however, the widened Zr−C−Zr angle of 132.7(1) and 134.0(3)°, respectively, and an unsymmetrical coordination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…For instance [(ZrCpMe)] 2 (μ-CH 2 ) 2 ] + [B(C 6 F 5 ) 4 ] − has an average distance of 2.234 Å, and for [ZrCp*-(C 2 B 9 H 11 )] 2 (μ-CH 2 ) the average distance is 2.182 Å. 32 13 C NMR resonance is shifted considerably upfield; however the coupling constant seen in the decoupled spectrum is typical of a bridging methylene ( 1 J C−H = 115 Hz). The attempted Hf reaction gave a 1 H NMR spectrum consisting of three resonances at δ = 2.10, 1.96, and −0.44 ppm in a 12:6:6 integral ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…For instance [(ZrCpMe)] 2 (μ-CH 2 ) 2 ] + [B(C 6 F 5 ) 4 ] − has an average distance of 2.234 Å, and for [ZrCp*-(C 2 B 9 H 11 )] 2 (μ-CH 2 ) the average distance is 2.182 Å. 32 13 C NMR resonance is shifted considerably upfield; however the coupling constant seen in the decoupled spectrum is typical of a bridging methylene ( 1 J C−H = 115 Hz). The attempted Hf reaction gave a 1 H NMR spectrum consisting of three resonances at δ = 2.10, 1.96, and −0.44 ppm in a 12:6:6 integral ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The compositiono f[ CH 2 (MgBr) 2 ]h as been further elucidated by in situ trapping experiments,f or example, the reactionw ith CO 2 to form CH 2 (CO 2 H) 2 or addition to olefins/carbonyls,h owever,t he isolation and characterization of the complex has remained elusive. [77][78][79][80][81] Ap otential decomposition pathway during the direct synthesis of such heteroleptic compounds involvest he formation of ethylene in Wurtz-type coupling reactions. Remarkably,b ye xtending the CH 2 2À unit to oligomeric (CH 2 ) n 2À ,W esterhausen and co-workers were able to access the correspondingt hf coordinated alkanediides [(thf) 2 Mg(CH 2 ) n ] x (n = 5, 8; x = 2; n = 4, 6; x = 1).…”
Section: Alkylidenesmentioning
confidence: 99%
“…IR-spectroscopic investigations of [MgCH 2 ] n werep erformed and furthers tudies revealed that the transfer of methylene groups from [MgCH 2 ] n to Cp 2 ZrMeCl affords the zirconium sandwichc omplexes[ Cp 2 Zr(X)(m-CH 2 )] 2 (X = Me, Cl) and [Cp 2 Zr(m-CH 2 ) 2 ] 2 . [81,86] [MgCH 2 ] n was also the subject of am atrix IR-spectroscopic study. [87] Noteworthy,t heoretical (DFT) calculations have been performed not only on the Mg II methylidene but also on the calcium analog [CaCH 2 ] n and other metal methylidenes.…”
Section: Reinera Nwander Studied Chemistry At Thementioning
confidence: 99%
See 2 more Smart Citations